2012
DOI: 10.1103/physreva.85.043604
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic Mach-Zehnder interferometer via an array of trapped ions

Abstract: We explore the possibility of implementing a Heisenberg-limited Mach-Zehnder interferometry via an array of trapped ions, which obey a quantum Ising model within a transverse field. Based upon adiabatic processes of increasing the Ising interaction and then decreasing the transverse field, we demonstrate a perfect transition from paramagnetism to ferromagnetic states, which can be used as the beam splitter for the multi-ion Mach-Zehnder interferometry. The achieved NOON state of the ions enables the Heisenberg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…This was among the first experimental realizations of quantum simulation. More recently, the study of Mach-Zehnder interferometry with an array of trapped ions was explored in (Hu et al, 2012).…”
Section: Interferometrymentioning
confidence: 99%
See 1 more Smart Citation
“…This was among the first experimental realizations of quantum simulation. More recently, the study of Mach-Zehnder interferometry with an array of trapped ions was explored in (Hu et al, 2012).…”
Section: Interferometrymentioning
confidence: 99%
“…Ions (Leibfried et al, 2002)*, (Hu et al, 2012;Lau and James, 2012) Photons (Aaronson and Arkhipov, 2011), (Broome et al, 2013)*, (Crespi et al, 2013;Spring et al, 2013;Tillmann et al, 2013)* Superconducting circuits (Liao et al, 2010;Zhou et al, 2008a) Other applications:…”
Section: Application Proposed Implementationmentioning
confidence: 99%
“…Ultracold trapped ions have been proposed to explore fundamental quantum principle and implement quantum information processing, 85,[190][191][192][193][194][195][196][197] quantum simulation 198,199 and quantum metrology. 24,30,85,143,144,200 Here, we give a brief introduction for some typical experiments of quantum metrology via ultracold trapped ions. In 2001, Meyer et al experimentally demonstrated that the sensitivity of rotation angle estimation with a Ramsey spectroscopy can be improved by using entangled trapped ions.…”
Section: Ultracold Trapped Ionsmentioning
confidence: 99%
“…A central goal of quantum metrology is how to enhance measurement precision with quantum resources such as spin squeezing and multiparticle entanglement. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] For a multiparticle system of cold atoms, it has been demonstrated that quantum entanglement and spin squeezing can be prepared by employing intrinsic inter-atom interactions or laser induced artificial inter-atom interactions. [27][28][29] Up to now, cold atoms have been widely used for implementing precision metrology, such as interferometers, [30][31][32] gyroscopes, 33 quantum clocks, [34][35][36] magnetic field detectors [37][38][39][40] and micro-gravity sensors.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Although the Cat state with six ions in chain has been feasible experimentally, 12 the generation of a large-scale Cat state with more qubits is still a fascinating challenge both theoretically and experimentally. The trapped-ion system is a promising candidate in this respect 6,7,12,13 due to the capability of 14-qubit entanglement in Ref. 14.…”
Section: Introductionmentioning
confidence: 99%